(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2020)
This article seeks to “connect the dots” of Maria Luiza Lacerda’s trajectory in the puppet theater, between memories and documents, from 1965 to 1989. Based on interviews and testimonies by the puppeteer herself and some women in the family, the article seeks to honor her for her contribution to the puppet theater in Brazil. From the creation of the pioneering group of puppet theater for children’s parties in Rio de Janeiro, Fura Bolo, to the group Revisão of experimentation in animation theater, Maria Luiza was present and active at the beginning of ABTB, experimented new languages and resources and created with great names in the puppet theater in Brazil.